2023
DOI: 10.1002/wnan.1884
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle‐assisted transdermal delivery of nanoparticles: Recent insights and prospects

Abstract: Transdermal delivery of drugs offers an interesting alternative for the administration of molecules that present certain troubles when delivered by the oral route. It can produce systemic effects or perform a local action when the formulation exerts an optimal controlled drug release or a targeted delivery to the specific cell type or site. It also avoids several inconveniences of the oral administration such as the hepatic first pass effect, gastric pH-induced hydrolysis, drug malabsorption because of certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 152 publications
0
2
0
Order By: Relevance
“…Researchers continue to explore and develop various types of microneedle technologies to optimize drug delivery for a wide range of medical applications. Details about microneedles research can be found in the recent review papers [39][40][41][42].…”
Section: Microneedlementioning
confidence: 99%
“…Researchers continue to explore and develop various types of microneedle technologies to optimize drug delivery for a wide range of medical applications. Details about microneedles research can be found in the recent review papers [39][40][41][42].…”
Section: Microneedlementioning
confidence: 99%
“…NPs have excelled as drug delivery carriers by encapsulating small molecules, peptides, proteins, and nucleic acids, being more versatile and carrying higher payloads than conventional drug delivery systems. In cancer therapy, NPs may show a higher selectivity through either passive or active targeting mechanisms, which allow them to overcome some of the inherent limitations of conventional drugs by improving drug localization, enhancing drug solubility, and reducing toxic side effects through controlled release at the target site [ 67 , 68 ]. Encapsulation of drug-loaded NPs within a hydrogel matrix has been used to prevent rapid drug release, both locally and systemically.…”
Section: Hydrogels and Nanoparticles—smart Platforms For Nanotheranos...mentioning
confidence: 99%
“…The integration of NCs will embrace the potential to transfigure the TDD for the management of skin ailments owing to their synergistic effect, which helps to boost patient compliance and enhance therapeutic outcomes . Thus, the nanocarriers (NCs) can be incorporated within the MNs to enhance bioavailability, reduce side effects, sustain the systemic concentration of the drug, and deliver the required drug concentration at the targeted site . On the other hand, the MNs deliver the therapeutics by circumventing the SC in a minimally invasive way.…”
Section: Introductionmentioning
confidence: 99%